Transition Metal Ion Implantation into Diamond-Like Carbon Coatings: Development of a Base Material for Gas Sensing Applications. (12th January 2015) - Markwitz, Andreas; Leveneur, Jérôme; Gupta, Prasanth; Suschke, Konrad; Futter, John; Rondeau, Morgane
Abstract : Micrometre thick diamond-like carbon (DLC) coatings produced by direct ion deposition were implanted with 30 keV Ar + and transition metal ions in the lower percentage (<10 at.%) range. Theoretical calculations showed that the ions are implanted just beneath the surface, which was confirmed with RBS measurements. Atomic force microscope scans revealed that the surface roughness increases when implanted with Ar + and Cu + ions, whereas a smoothing of the surface from 5.2 to 2.7 nm and a grain size reduction from 175 to 93 nm are measured for Ag + implanted coatings with a fluence of1.24 × 10 16 at. cm −2 . Calculated hydrogen and carbon depth profiles showed surprisingly significant changes in concentrations in the near-surface region of the DLC coatings, particularly when implanted with Ag + ions. Hydrogen accumulates up to 32 at.% and the minimum of the carbon distribution is shifted towards the surface which may be the cause of the surface smoothing effect. The ion implantations caused an increase in electrical conductivity of the DLC coatings, which is important for the development of solid-state gas sensors based on DLC coatings.